P85 Access to and experiences of remote HIV clinical services in high-income settings: a scoping review. (16th June 2022) - Nicholls, Emily Jay; Tariq, Shema; Lloyd, Karen; Gibbs, Jo
Abstract : Background: Remote delivery of HIV services (often facilitated by digital technology) has increased over recent years, especially in response to the COVID-19 pandemic. Using scoping methods, we synthesise current knowledge about remote HIV healthcare services. Methods: We systematically searched literature using multiple databases, supplementing this with searches of grey literature. We included papers reporting on empirical studies in high income countries (OECD) of remote HIV healthcare delivery by digital technology including mobile apps, video, SMS and telephone. We extracted data using a standardised tool and analysed data thematically. Results: A large proportion of studies focus on interventions supporting antiretroviral therapy adherence, often via mobile apps or SMS. There has been a recent uptick in work describing remote routine HIV clinical appointments in the context of COVID-19. There was a dearth of evidence on the impact of remote HIV healthcare services on clinical and patient-reported outcomes, as well as factors shaping access to remote HIV healthcare services. Discussion: There is an increasingly large body of work investigating remote HIV healthcare services, much of it focusing on adherence support. Less is known on barriers to and facilitators of remote HIV healthcare service provision and access, and how these services impact patient experience and outcomes. Given the enduring change to models of HIV healthcare as a result of COVID-19, we urgently require a robust evidence-base to inform inclusive, equitable and effective service design.